LESM: a laser-driven sub-MeV electron source delivering ultra-high dose rate on thin biological samples. (14th June 2016) - Labate, L; Andreassi, M G; Baffigi, F; Bizzarri, R; Borghini, A; Bussolino, G C; Fulgentini, L; Ghetti, F; Giulietti, A; Köster, P; Lamia, D; Levato, T; et al.
Abstract: We present a laser-driven source of electron bunches with average energy 260 k e V and picosecond duration, which has been setup for radiobiological tests covering the previously untested sub-MeV energy range. Each bunch combines high charge with short duration and sub-millimeter range into a record instantaneous dose rate, as high as 10 9 G y s − 1 . The source can be operated at 10 H z and its average dose rate is 35 m G y s − 1 . Both the high instantaneous dose rate and high level of relative biological effectiveness, attached to sub-MeV electrons, make this source very attractive for studies of ultrafast radiobiology on thin cell samples. The source reliability, in terms of shot-to-shot stability of features such as mean energy, bunch charge and transverse beam profile, is discussed, along with a dosimetric characterization. Finally, a few preliminary biological tests performed with this source are presented.